Close-up : great cinematic performances. Volume 2, International - Pomerance, Murray, 1946-; Stevens, Kyle (Edinburgh : Edinburgh University Press, 2018)
The first systematic analysis of current debates surrounding the role of practice in political theory.
Chapter 26 Gael García Bernal in The Motorcycle DiariesThe cast; The contributors; Index.
Online resource; title from PDF title page (EBSCO, viewed May 30, 2018).
Includes bibliographical references and index.
JSTOR
Keywords: Motion picture acting; Motion picture acting -- Case studies; Motion pictures -- History; Motion pictures -- History -- Case studies; Art de l'acteur au cinéma.; Art de l'acteur au cinéma -- Études de cas; Cinéma -- Histoire; Cinéma -- Histoire -- Études de cas; PERFORMING ARTS -- Reference; PERFORMING ARTS / Acting & Auditioning; Motion picture acting; Motion pictures; Case studies; History